2004
DOI: 10.1001/archsurg.139.10.1079
|View full text |Cite
|
Sign up to set email alerts
|

Men With Breast Cancer Have Better Disease-Specific Survival Than Women

Abstract: Hypothesis:Male breast cancer patients have better disease-specific survival than carefully matched female breast cancer patients.Design: Retrospective study.Setting: University hospital. Patients and Methods:Each man in the breast cancer database at Columbia-Presbyterian Medical Center (New York, NY) between the years 1980 and 1998 was matched with a woman. Matching was done based on age and date of diagnosis, stage, and primary histologic findings. Main Outcome Measures:The overall survivals and disease-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 26 publications
2
44
2
11
Order By: Relevance
“…However, when matched for stage, age and hormone receptor status, male and female breast cancer patients show the same over-all survival pattern [16]. Stage, nodal status (positivity and number of involved nodes), size and hormone receptor status are considered as important prognostic factors [12].…”
Section: Resultsmentioning
confidence: 99%
“…However, when matched for stage, age and hormone receptor status, male and female breast cancer patients show the same over-all survival pattern [16]. Stage, nodal status (positivity and number of involved nodes), size and hormone receptor status are considered as important prognostic factors [12].…”
Section: Resultsmentioning
confidence: 99%
“…Sabe-se que o tempo ideal de uso do tamoxifeno é de, no mínimo, cinco anos, sendo esse o período que deve ser utilizado para obtenção do seu melhor efeito 4,8 . É importante ressaltar que a terapia hormonal provavelmente deva ser indicada apenas em tumores positivos para receptores hormonais 14,26 . Os estudos sobre o tratamento adjuvante, incluindo os inibidores da aromatase (anastrazol e letrozol), ainda são insuficientes.…”
Section: Tratamentounclassified
“…O comprometimento dos linfonodos axilares é um fator prognóstico negativo e homens com linfonodos positivos têm risco de morte 50% maior, em relação aos casos com linfonodos negativos 4,27 . A ideia de que o câncer de mama masculino tem pior prognóstico do que o feminino perdurou por longos períodos na literatura 26 . Contudo, com a continuidade dos estudos, demonstrou-se que quando homens e mulheres com câncer de mama são pareados quanto à idade e ao estadiamento dos tumores, apresentam prognósticos similares.…”
Section: Prognósticounclassified
See 1 more Smart Citation
“…However, recent studies revealed that MBC and FBC patients have a similar prognosis (13 -15). One study showed that although overall survival (OS) was equivalent between both the sexes, diseasespecific survival was significantly better in MBC than in FBC (16). Thus, there is no consensus on the relationship between the patient's sex and prognosis in breast cancer.…”
Section: Introductionmentioning
confidence: 99%